Instilling Religious Literacy for Learners and Its Significance to Education (مجلة ديالى للبحوث الانسانية, 2023)
Abstract:Educational process is inseparable from reading and writing activities. Reading and writing activities are parts of literacy. One type of literacy is religious literacy. This study investigates the instillation of religious literacy as an educational alternative for students with the aims of finding (1) efforts conducted by schools to instill religious literacy for learners, and (2) significances of religious literacy for students in educational activities. Data collection techniques in this qualitative research are observation and interview. Researchers observed religious literacy activities carried out by academic communities of SD Muhammadiyah Barru consisting of 180 students, 6 classroom teachers, 2 subject teachers, 1 educational staff, and 1 school principal. To obtain data about the benefits of religious literacy in educational activities for learners, researchers conducted in-depth interviews with the school principal, the teacher of Islamic Religious Education, and 3 students selected. For data analysis, researchers used three steps, namely data reduction, data display, and drawing conclusions. Researchers found that the efforts to instill religious literacy at SD Muhammadiyah Barru were: (1) habituation, (2) development, and (3) learning activities. The results of interviews and discussion indicate the significances of religious literacy for learners in educational activities namely (1) religious literacy activities add students’ insight and increase students’ knowledge, and (2) religious literacy activities expedite the teaching and learning process.